The Effect Of E-Commerce Tax Complexity And Tax Sanctions On Online Marketplace Taxpayer Compliance With Gender As A Modertion Variable - Marizka Amelia; Prastiwi, Dewi; Palil, Mohd Rizal (International Environmental Conferrence on Biosustainability Advancement, 2024)
This study aims to determine the effect of e-commerce tax complexity and tax sanctions on online marketplace taxpayer compliance with gender as a moderating variable. This study uses primary data with data collection methods in the form of questionnaires distributed via gform. The population in this study is 2,868,178 e-commerce players in Indonesia (bps.go.id). The sample in this study used the slovin method with a total of 100 respondents. The analysis technique used in this study is SEM-PLS using Smart-PLS. The results of the study show that the complexity of e-commerce taxes has a positive effect on online marketplace taxpayer compliance, tax sanctions have no effect on online marketplace taxpayer compliance. Gender can moderate the complexity of e-commerce taxes on online marketplace taxpayer compliance with a negative relationship. In addition, Gender cannot moderate tax sanctions against online marketplace taxpayer compliance.